PENDIDIKAN ISLAM PADA MASA KEBANGKITAN (Gerakan Intelektual Muslim di Kalangan Syiah Isma’iliyah dan Dinasti Safawy) - Pasmah Chandra (Jurnal Pendidikan "EDUKASIA MULTIKULTURA", 2020)
The purpose of this study was to determine the Muslim intellectual movement among the Ismaili Shiites and Safawy Dynasty. The research method used is the method of library research or library research. From the results of the study it can be seen that the formation of the Shia Ismailiyah group is more due to differences in the determination of the successor to Imam Ja'far Sadiq as. In 148 AH / 765 AD in the city of Kufa some Shi'ites separated themselves. This separation was closely related to the struggle against the Abbasid dynasty. The idea behind the struggle is the belief that a government based on justice can only be justified if it is carried out behind the leadership of Ismail bin Ja'far (Imam Ja'far Sadiq's eldest son. While the Safawy dynasty came from a tarekat movement that stood in Ardabila, a city in Azerbaijan, the Congregation was given the name Safawyyah Tarekat, which was taken from the name of its founder Safi Al-din (1252-1334 AD), and the name continued to be preserved until the tarekat became a political movement.In fact, the name continued to be preserved after this movement succeeded in establishing the Kingdom. According to Harun Nasution, in Persia a dynasty emerged which later became a large kingdom in the Islamic world, this dynasty originated from a Sufi Shaykh Ishak Safiuddin from Ardabila in Azerbaijan.